Kolaborasi Peran Guru dan Orang Tua dalam Penerapan Disiplin Positif (IAI Sunan Giri Trenggalek, 2025)
Education can take place at home, school or in the community environment which is known as the three centers of education. The educational trilogy expressed by Ki Hajar Dewantara is: